The Influence of Cultivating Positive Emotions on the Academic Performance of High School Students (Journal of Educational Sciences, 2025)
In the learning process of students: The core role of emotional factors and their potential influence on the academic achievements of senior high school students. Emotions play a vital role in the learning life and have an undeniable and far-reaching impact on students' academic performance. Senior high school students are in a sensitive period of rapid physical and mental development. They not only encounter heavy academic pressure but also need to cope with complex psychological changes, which makes emotional problems particularly prominent among this group. Positive emotions, as a positive psychological experience, can exert a significant positive effect on the cognitive processes, learning motivation, and allocation of psychological resources of senior high school students, thereby further promoting the enhancement of their academic achievements. To understand this phenomenon more deeply, based on the relevant theoretical framework of educational psychology, this paper conducts a comprehensive and in-depth exploration of the complex relationship between the cultivation of positive emotions and the academic achievements of senior high school students. This paper aims to provide scientifically based and operational reference suggestions for high school education and teaching practices through rigorous academic analysis, in order to assist senior high school students in managing their emotions more effectively and achieving more excellent academic achievements. 254 schoolchildren took part in the survey.Key words:Cultivation of positive emotions, High school student, Academic performance